Intracaesarean forceps application - Verma, Mansi; Keskar, Jagruti; Bhalerao, A. N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In a time when repeat caesarean deliveries are becoming more frequent, more elective LSCS are being performed and floating vertex are commonly encountered. Sometimes fundal pressure is not adequate, and the physician needs to use instrument (vaccum/forceps) to deliver the head. The objective of the present study is to evaluate maternal and neonatal complications of intracaesarean forceps application Methods: This was an interventional study which was conducted in OBGY department of Sassoon General Hospital, Pune for 1 year. 75 cases including both emergency and elective sections were included in the study, in which intracaesarean outlet forceps was applied. Results: Out of 75 cases, maternal complications were seen in 5 cases with uterine incision extensions being the commonest (4%). Neonatal complications were seen in 3 cases, with minor facial injuries due to pressure of forceps being commonest (2.6%). Conclusions: Intracaesarean forceps when applied skillfully can be effective, fast and safe technique of delivering fetal head in this rising trend of caesarean sections.